Sources of Microplastics in the Environment and Human Exposure Routes: A Review - Aran Akbari; Kamran Taghavi; Jalil Jaafari (Caspian Journal of Health Research, 2024)
In this study, the sources of microplastics in the environment, the ways of human exposure to microplastics, how to deal with them, and the policies and laws of different countries in this regard are discussed. Most of the microplastic pollution comes from textiles, tires and urban dust, which make up more than 80% of the microplastics in the environment. The human body is exposed to microplastics through eating food containing microplastics, inhaling microplastics in the air, and skin contact with these particles in products, textiles, or in dust. The main route of human exposure to microplastic particles in human diet is food and drink. Microplastics can enter food during food processing, storage, transportation and packaging process. Airborne microplastics are an underestimated hazard, potentially reaching deep into human lungs because they can pass through the defensive respiratory system. Humans may also be exposed to microplastics through skin contact, following the atmospheric fallout, in this case hair follicles, sweat glands or damaged skin are all ways of entry. Some researchers have suggested burning plastics and recovering the resulting energy. Nevertheless, plastic recycling is considered a more efficient solution because this method reduces the amount of plastic waste produced as opposed to burning.